2011
DOI: 10.1002/msj.20229
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Environmental Chemicals

Abstract: Childhood and adolescent rates of obesity and overweight are continuing to increase in much of the world. Risk factors such as diet composition, excess caloric intake, decreased exercise, genetics, and the built environment are active areas of etiologic research. The obesogen hypothesis, which postulates that prenatal and perinatal chemical exposure can contribute to risk of childhood and adolescent obesity, remains relatively underexamined. This review surveys numerous classes of chemicals for which this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 190 publications
(258 reference statements)
1
116
2
1
Order By: Relevance
“…Much research has been undertaken to study the link between any one individual factor and obesity. [6][7][8][9][10][11][12][13][14] For example, metabolic risk factors such as diabetes have been shown to be linked to obesity, and there is growing research exploring the associations between chemical exposures and diabetes. 15,16 However, the inter-relationships between stressors are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been undertaken to study the link between any one individual factor and obesity. [6][7][8][9][10][11][12][13][14] For example, metabolic risk factors such as diabetes have been shown to be linked to obesity, and there is growing research exploring the associations between chemical exposures and diabetes. 15,16 However, the inter-relationships between stressors are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies concerned with exposure to these POPs did not prove the association with the obesity of children, adolescents, or adults. Contrary results were reported only on the basis of one prospective study of among Belgian children that observed a positive correlation between PCBs in umbilical cord levels and body mass index values [72]. Weight-gain effect was also observed in rats [127].…”
Section: +mentioning
confidence: 71%
“…The results reported by [72] have evidenced that lead exposure may also influence the risk of obesity. Lead levels in the teeth of children in the United States were positively associated with their Body Mass Index (BMI).…”
Section: Heavy Metals: Neuroendocrine Disruptions and Obesitymentioning
confidence: 99%
“…As recently reviewed in detail [48], no consistent association has been found between foetal exposure to PCBs and obesity during childhood or early adult life [49][50][51][52][53], whilst a majority of the studies in which foetal exposure to DDE was measured reported positive relationships with later BMI or body weight [50][51][52][53][54]. It should be noted, however, that only one of these studies [50] evaluated obesity during a prolonged follow-up (20-50 years), so the full potential of these mother-child studies remainsunclearatpresent.…”
Section: Obesitymentioning
confidence: 99%